2013
DOI: 10.1186/1477-7525-11-37
|View full text |Cite
|
Sign up to set email alerts
|

Screening for anxiety disorders in patients with coronary artery disease

Abstract: BackgroundAnxiety disorders are prevalent and associated with poor prognosis in patients with coronary artery disease (CAD). However, studies examining screening of anxiety disorders in CAD patients are lacking. In the present study we evaluated the prevalence of anxiety disorders in patients with CAD and diagnostic utility of self-rating scales for screening of anxiety disorders.MethodsFive-hundred and twenty-three CAD patients not receiving psychotropic treatments at initiation of rehabilitation program comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 43 publications
3
64
1
1
Order By: Relevance
“…6,15 However there are other studies which has reported higher prevalence of GAD. 7,8,9,10,11,12,13,14,16,17 The study reported higher prevalence of GAD among females, illiterates and those belonging to lower socio economic class. 6,7,9,11,12,14,15 …”
Section: Discussionmentioning
confidence: 88%
“…6,15 However there are other studies which has reported higher prevalence of GAD. 7,8,9,10,11,12,13,14,16,17 The study reported higher prevalence of GAD among females, illiterates and those belonging to lower socio economic class. 6,7,9,11,12,14,15 …”
Section: Discussionmentioning
confidence: 88%
“…Pri bolnikih z akutnim koronarnim dogodkom je depresija povezana z 2-do 2,7-krat večjim tveganjem za smrt. Ameriško združenje kardiologov je tako opredelilo depresivnost kot dejavnik tveganja za slabši izid po akutnem miokardnem infarktu, zato je priporoči-lo rutinsko testiranje za depresivnost pri bolnikih s koronarno boleznijo (1)(2)(3)(4).…”
Section: Uvodunclassified
“…Subjects from both experimental groups completed the Spielberger (Bunevicius et al, 2013;Devier et al, 2009; for a detailed review, see Glozman, 2004;Özpelit et al, 2015). In our study, we have indeed utilized STAI scores as a continuous variable to determine possible correlations with RePi.…”
Section: Anxiety Measuresmentioning
confidence: 99%